1997
DOI: 10.1002/(sici)1097-0290(19970620)54:6<549::aid-bit6>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

An efficient model development strategy for bioprocesses based on neural networks in macroscopic balances

Abstract: In the serial gray box modeling strategy, generally available knowledge, represented in the macroscopic balance, is combined naturally with neural networks, which are powerful and convenient tools to model the inaccurately known terms in the macroscopic balance. This article shows, for a typical biochemical conversion, that in the serial gray box modeling strategy the identification data only have to cover the input‐output space of the inaccurately known term in the macroscopic balances and that the accurately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…The optimized performance based on neural models is better than that achieved through model-based control. However, neural networks have poor physiological fidelity and extrapolation capability, they require carefully screened data, and they may require considerable amount of training for complex systems (Hassoun 1995;Haykin 1998;van Can et al 1997). These weaknesses may be reduced by using combinations of neural networks and mathematical models.…”
Section: Description Of Phb Biosynthesismentioning
confidence: 95%
See 3 more Smart Citations
“…The optimized performance based on neural models is better than that achieved through model-based control. However, neural networks have poor physiological fidelity and extrapolation capability, they require carefully screened data, and they may require considerable amount of training for complex systems (Hassoun 1995;Haykin 1998;van Can et al 1997). These weaknesses may be reduced by using combinations of neural networks and mathematical models.…”
Section: Description Of Phb Biosynthesismentioning
confidence: 95%
“…While native PHB is rather brittle and has a melting point (180°C) close to its thermal degradation temperature (200°C), these properties improve significantly on copolymerization with other polymers, notably polyhydroxyvalerate (van der Walle et al 2001). Then, PHB has many properties comparable to those of large-scale chemically synthesized polyethylene (PE) and polypropylene (PP ;Doi 1990;Steinbuchel 1996).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Applications to a number of monotonic fermentations [3,19,20] have shown their superiority over their components in stand-alone mode. A recent application [13] has shown that a hybrid filter can also outperform algorithmic filters for oscillating cultures of S. cerevisiae.…”
Section: Noise Filters For Bioreactorsmentioning
confidence: 99%